2020
DOI: 10.3390/microorganisms8071084
|View full text |Cite
|
Sign up to set email alerts
|

Batch and Continuous Lactic Acid Fermentation Based on A Multi-Substrate Approach

Abstract: The utilisation of waste materials and industrial residues became a priority within the bioeconomy concept and the production of biobased chemicals. The aim of this study was to evaluate the feasibility to continuously produce L-lactic acid from different renewable substrates, in a multi-substrate strategy mode. Based on batch experiments observations, Bacillus coagulans A534 strain was able to continuously metabolise acid whey, sugar beet molasses, sugar bread, alfalfa press green juice and tapioca starch. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 44 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Ninety percent of lactic acid produced worldwide is obtained through sucrose fermentation (Cock and Stouvenel, 2005) from sugarcane molasses (Ahmad et al, 2020;González-Leos et al, 2020) or sugarbeet juice (Olszewska-Widdrat et al, 2020;Malik et al, 2019;Kotzamanidis et al, 2002), but Abedi and Hashemi (2020) reported other substrates can be used such as lignocellulosic materials supplemented with nitrogen sources. It is also possible to use lactose from whey and glucose from hydrolyzed starch (Iskandar et al, 2019;Bulut et al, 2004;Lazarova and Peeva, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ninety percent of lactic acid produced worldwide is obtained through sucrose fermentation (Cock and Stouvenel, 2005) from sugarcane molasses (Ahmad et al, 2020;González-Leos et al, 2020) or sugarbeet juice (Olszewska-Widdrat et al, 2020;Malik et al, 2019;Kotzamanidis et al, 2002), but Abedi and Hashemi (2020) reported other substrates can be used such as lignocellulosic materials supplemented with nitrogen sources. It is also possible to use lactose from whey and glucose from hydrolyzed starch (Iskandar et al, 2019;Bulut et al, 2004;Lazarova and Peeva, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon sources are the key factor affecting LA production costs. Most often, a plentiful, affordable raw material, such as agricultural residues and industrial by-products like molasses, acid whey, green alfalfa juice, food wastes, etc., was employed as a substrate for LA fermentation [5][6][7][8][9][10]. Other fermentation feedstock, such as starchy and cellulosic materials, i.e., tapioca starch, sweet sorghum juice, potato, wheat, rye-barley, malt, rice, xylan-derived sugars, galactan, and lignin were studied for cost-effective LA production processes [3,8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[6], Lactobacillus casei CCDM 198 [20], Lactobacillus plantarum [3], L. rhamnosus ATCC 10863 [9]. L. rhamnosus LA-04-1 [21], Bacillus coagulans A534 [8], Enterococcus mundtii QU 25 [22], and Lactococcus lactis subsp. lactis NBRC 12007 [23].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit preservation process is a sweet fermentation (called "Chair Im"). After fermentation, most of the ingredients in the fruit are sugars; the liquid waste contains lactic acid (Olszewska-Widdrat et al, 2020). If waste contaminates rivers or reservoirs, it will result in an algal boom or eutrophication because liquid waste is a source of energy for environmental microorganisms (Vollstedt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%